Intermediate English Conversation Training for Indonesian Migrant Workers - Elisabeth Marsella; Vinindita Citrayasa; Lucia Bening Parwita Sukci (LPPM IKIP PGRI Pontianak, 2023)
This program aims to improve Indonesian migrant workers’ English conversation proficiency, run by Indonesian Diaspora Network Global. The program helped 35 workers from Hong Kong, Taiwan, Singapore, and Malaysia. Universitas Atma Jaya Yogyakarta assisted IDN Global with teaching materials and facilitators composed of three lecturers and three students. Understanding the workers’ need to master English skills, an intermediate English course program was designed with food as its theme. The program was conducted via Zoom every Wednesday from 21.00-23.00 Indonesian Western Time. Each meeting consisted of a lead-in, vocabulary activities, group discussion, class discussion, and reflection. Based on the reflection, interview, and the participants’ presentation activity, this program had been more conducted with a better structure in developing the participants’ involvement, confidence, and ability to communicate in English.